From an atomistic study of olivine under pressure to the understanding of the macroscopic energy release in earthquakes - Maurizio Mattesini; Carolina López Sánchez; Elisa Buforn; Agustín Udías; Jaime de la Serna Valdés; Hernando Tavera; Carmen Pro (Geosystems and Geoenvironment, 2023)
We present a multi-disciplinary study of the rupture process of deep- and intermediate-depth earthquakes in the subducting slab that develops beneath the Peruvian-Brazilian region. This contemplates the understanding of the atomistic fracture mechanism in an olivine model, its energetics budget, and the bridging of these results to the available seismic observables. A theoretical description of the stress-strain curves for the subducting material is initially provided as a key element to discern whether the rupture mechanism changes with depth or not. To this purpose, atomistic modelling was carried out through ab initio techniques for the forsterite olivine at different pressure ranges. The achieved stress-strain curves were compared to the average moment-scaled functions obtained for 43 intermediate (50 km < h < 200 km) and very deep earthquakes (500 km < h < 700 km) at the Peruvian-Brazilian subduction zone. It is found that at both depths operate a common atomistic rupture mechanism that is based on the gliding of the {001} crystal planes. Although the velocity of stress release changes with depth, this finding helps to clarify the controversial rupture process for very deep earthquakes at subduction zones. Likewise, efforts were directed to quantify the total amount of energy freed during an earthquake. Test calculations were carried out for several deep earthquakes providing rupture energy of six orders of magnitudes larger than the observable radiated seismic energy. This indicates that there might be space for redefining the commonly accepted order of magnitude for the seismic efficiency coefficient.